Challenges in using frog VLE in teaching english to ESL learners: a review of past studies - Siti Sarah Shazali; Harwati Hashim (RedWhite Press, 2018)
In the era of 21st century teaching and learning, technology has been widely used among educators especially in teaching of English Language. Many studies have proven that teaching through the use of technology such as media socials, video conferencing, Frog Virtual Learning Environment and other mediums help in increasing the knowledge and usage of the English Language. This paper aims to review challenges encounter by teachers when using Frog VLE in teaching English to English as a Second Language (ESL) learners particularly in primary and secondary schools in Malaysia. This paper reviews journal articles, books and other researches to identify the challenges in using technology especially the use of Frog VLE. The review of past studies has shown that challenges did occur during the implementation of Frog VLE. Thus, this paper puts forth a proposition that more research should be conducted on teachers’ perceptions towards the use of Frog VLE in classroom teaching. Add on sentence to conclude and highlight the implication.